1943
DOI: 10.1152/ajplegacy.1943.140.2.260
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Administration of Estrogen on the Mechanism of Ascorbic Acid Excretion in the Dog

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

1945
1945
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…The present results reinforce this view, since alterations in electrolyte excretion sometimes preceded changes in clearances; moreover, in diabetes insipidus, clearances and electrolyte excretion did not alter in the same sense. It follows from the work of Thorn & Engel (1938), of Selkurt et al (1943) and from the present work that the effect of stilboestrol on renal function is not essentially dependent on a rise in G.F.R. or R.P.F., or the presence of either adrenals or gonads, but that the response is altered by interference with the supraoptico-hypophysial system.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…The present results reinforce this view, since alterations in electrolyte excretion sometimes preceded changes in clearances; moreover, in diabetes insipidus, clearances and electrolyte excretion did not alter in the same sense. It follows from the work of Thorn & Engel (1938), of Selkurt et al (1943) and from the present work that the effect of stilboestrol on renal function is not essentially dependent on a rise in G.F.R. or R.P.F., or the presence of either adrenals or gonads, but that the response is altered by interference with the supraoptico-hypophysial system.…”
Section: Discussionsupporting
confidence: 56%
“…Measurements of renal clearances showed that stilboestrol caused some rise in G.F.R. as was found by Selkurt et al (1943), but an even greater rise in R.P.F. The changed clearances, like the change in water and Na excretion, lasted for a number of days.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations